Real Effective Exchange Rate Misalignment in the Euro Area: A Counterfactual Analysis. Issue 1 (26th November 2015) - El‐Shagi, Makram; Lindner, Axel; von Schweinitz, Gregor
Abstract: The European debt crisis has revealed severe imbalances within the Euro area, sparking a debate about the magnitude of those imbalances, in particular concerning real effective exchange rate misalignments. We use synthetic matching to construct a counterfactual economy for each member state in order to identify the degree of these misalignments. We find that crisis countries are best described as a combination of advanced and emerging economies. Comparing the actual real effective exchange rate with those of the counterfactuals gives evidence of misalignments before the outbreak of the crisis: all peripheral countries appear strongly and significantly overvalued.